Procyclicality of Labour Productivity in Polish Regions in 1995-2013 - Kuźmar, Sławomir (Studia Oeconomica Posnaniensia, 2017)
The procyclicality of labour productivity is one of the basic stylized facts of economics. The aim of the paper is to analyse the procyclical properties of labour productivity in Polish regions in the years 1995-2013. In the theoretical part, a critical analysis of the literature is used to identify the possible determinants of the analysed effect. It was found that three of them are usually mentioned: technological shocks, increasing returns to scale and labour hoarding. In the empirical part, an assessment of labour productivity procyclical behaviour was performed. The obtained results confirm that labour productivity in some Polish regions is procyclical.